A folded higher‐mode slot antenna with enhanced bandwidth and radiation pattern reshaping. Issue 9 (7th June 2021) - Xu, Yanhui; Zhu, Lei; Liu, Neng‐Wu
Abstract: In this article, an approach to reshape the radiation pattern of the 1.5 λ ‐mode of the slot antenna is proposed. Unlike previous works on slot antenna operating at the fundamental mode with a broadside radiation performance, the proposed slot antenna holds four symmetric radiation beams by resonating at its radiative λ ‐ and 1.5 λ ‐mode. Initially, by folding the straight slot radiator at one short‐ended terminal, radiation patterns in H‐plane of the 1.5 λ ‐mode could be significantly reshaped from the broadside beam into four symmetric radiation beams, while that of the λ ‐mode almost remains unchanged. Then, a pair of slot stubs is symmetrically introduced to further improve the bandwidth of multibeam radiation performance. An antenna prototype is finally fabricated and measured to validate the predicted performance. Good agreement between the simulated and measured results is observed. The antenna operates in a frequency range of 3.64 to 3.96 GHz with S 11 lower than − 10 dB under dual‐mode resonance. And four symmetric beams for radiation have been successfully obtained at the directions of 40 °, − 40 °, 140 °, and − 140 ° with respect to the broadside direction across the whole operating bandwidth.